Yinyang bipolar relativity : a unifying theory of nature, agents and causality with applications in quantum computing, cognitive informatics and life sciences - Zhang, Wen-Ran, 1950- (Hershey, PA : Information Science Reference, 2011)
"This book presents real-world applications of YinYang bipolar relativity that focus on quantum computing and agent interaction. This unique work makes complex theoretical topics, such as the ubiquitous effects of quantum entanglement, logically comprehendible to a vast audience"--
Includes bibliographical references and index.
Keywords: Unified field theories